Challenges of covid-19 crisis on Malaysia’s education sector - Wong Sing Yun (Journal of Social Sciences and Humanities, 2023)
This paper aims to provide a comprehensive overview of the development of Malaysia’s education policies over the years. In addition, this study seeks to further draw attention to the recent implications of COVID-19 on Malaysia’s education sector. The education policies developed in the past decades have highlighted that Malaysia Government had continuously shown tremendous support and has put high emphasis on the education sector. However, the pandemic crisis has disrupted learning and posed new challenges to the education system and the policies developed in the past. Therefore, this paper will employ a narrative review to draw lessons based on the observations retrieved from existing literature and various secondary sources such as policy briefs, media, commentaries, and documentaries of related evidence on the challenges of the pandemic crisis to the education system and its policy. In addition, the review will also shed light on the policies' recommendations in adapting to the new normal and establishing this as a new research direction for future studies.